Effect of Denture Cleanser on the Physico-Mechanical Properties of Injection-Molded Thermoplastic Polyamides Denture Base Material: A preliminary Study - Hazem Mofreh Altarawneh; Mohammed Nasser Alhajj; Nosizana Mohd Salleh; Aeman H. H. Elkezza; Wan Adida Mahmood (University of Zagreb. School of Dental Medicine, 2023)
Objectives: This study aimed to assess the color stability, surface roughness, and flexural properties of the injection-molded thermoplastic polyamide Vertex ThermoSens denture base resin following a 3-minute immersion in Polident 3-minute denture cleanser. Methods: Sixty specimens (Vertex ThermoSens) were processed and divided into two main groups (n = 30) based on the type of test. Group 1 was further subdivided into two subgroups (n = 15): the control group immersed in distilled water (G1DW) and the test group immersed in Polident cleanser solution (G1PD). Group 2 was divided into three subgroups: a non-immersed group (G2None), a group immersed in distilled water (G2DW), and a group immersed in Polident cleanser solution (G2PD). Color change (∆E) and surface roughness measurements were conducted for group 1, and flexural modulus (E) test was performed for group 2. The CIE Lab* formula was utilized to calculate ∆E. An optical 3D surface analyzer and a three-point bending test were employed for surface roughness and E assessments, respectively. Data were subjected to statistical analysis using a paired-sample t-test for differences within each group before and after immersion. Furthermore, independent-sample t-tests and one-way ANOVA were conducted to analyze differences between groups. A significance level of P < 0.05 was considered. Results: The results revealed a slight, statistically insignificant (P > 0.05) ∆E in all color components (L*, a*, b*) after immersion in distilled water. However, after immersion in the denture cleanser, only the L* component exhibited a statistically significant ∆E (P = 0.002), which was slight in magnitude. Additionally, a significant difference was found in the ∆E between G1DW and G1PD, with G1PD showing a higher change (P = 0.007). A significant increase in surface roughness after immersion was observed in G1PD (P = 0.017), with a notable difference between G1DW and G Conclusion: Denture cleansers have the potential to modify the properties of thermoplastic polyamide resin. Further research is needed to explore the clinical implications of these observed changes on denture performance. 1PD. However, the E remained unaffected (P = 0.537).